Coletividade, subjetividades e diferenças: a participação política das pessoas com deficiência na universidade pública - Pereira, Antônio Polli Mendes (Universidade Federal de São Carlos, 2025)
This theoretical essay aims to reflect, through the lens of Hannah Arendt and Michel Foucault, on the political participation of people with disabilities in public universities as subjective and collective actors participating in political arenas of debate. The study considers disability not as an innate and immutable concept, but as the result of a complex discursive process involving multiple groups, interests and dialectics that bring into play the participation of people with disabilities in various social contexts. In this approach, we sought to understand how the advance of modernity and its scientific rationalization contributed to the emergence of the category that, with a strong influence from the medical field, we now call disability. It begins with a presentation of the English social movement Disability Studies, which took place in the 1960s and 1970s and contributed to shifting the conception of disability from biomedical principles to a political and social approach. It concludes with contemporary discussions about the public university and its political and cultural aspects for the participation of people with disabilities.
Collectivity, subjectivities and differences: the political participation of people with disabilities in public universities
Keywords: Modernidade; Concepções biomédicas; Filosofia política; Participação política; Educação superior; CIENCIAS HUMANAS::EDUCACAO